Green Hydrogen Energy Systems - Arsalis, Alexandros; Kourougianni, Fanourios; Olympios, Andreas V.; Konstantinou, Charalampos; Yiasoumas, Georgios; Papanastasiou, Panos; Vellayani, Aravind Purushothaman; Kalogirou, Soteris A.; Georghiou, George E. (My University, 2025)
Green Hydrogen Energy Systems explores the vital technologies and methods for generating, storing, and utilizing green hydrogen. By adopting an energy systems approach, the book offers a comprehensive review of green hydrogen systems, integrating principles, configurations, progress, and applications, bolstered by technoeconomic analyses and performance data. Addressing common challenges, it explains processes for developing and constructing basic and advanced green hydrogen systems. The book details the fundamentals of hydrogen technologies, including thermodynamics, kinetics, energy loss mechanisms, and costs. It covers aspects such as heat release, clean water usage in electrolyzers, system configurations, and includes real-world performance data, case studies, hydrogen hubs, safety, and economics.